Protocol for generating a pancreatic cancer organoid associated with heterogeneous tumor microenvironment - Kenta Takeuchi; Shunsuke Tabe; Yuya Yamamoto; Kenta Takahashi; Megumi Matsuo; Yasuharu Ueno; Masayuki Ohtsuka; Soichiro Morinaga; Yohei Miyagi; Tomoyuki Yamaguchi; Naoki Tanimizu; Hideki Taniguchi (STAR Protocols)
Summary: Pancreatic ductal adenocarcinoma (PDAC) organoids that simulate the tumor microenvironment (TME) are an effective tool to identify how TME affects PDAC malignancy. We present a protocol for generating a fused pancreatic cancer organoid (FPCO) that partly reproduces the TME, including heterogeneous cancer-associated fibroblasts (CAFs), using patient-derived PDAC cells and human-induced pluripotent cell-derived endothelial and mesenchymal cells. We also describe the procedure for analyzing FPCO characteristics. FPCO can provide a platform for establishing a reliable drug screening system.For complete details on the use and execution of this protocol, please refer to Takeuchi et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.